2002
DOI: 10.1186/1471-2202-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel memory mutants in Drosophila: Behavioral characteristics of the mutant nemy P153

Abstract: Background: Starting from Benzer's initiative, the approach of forward genetics has been widely used to isolate mutations affecting learning and memory. For this aim, mainly the odor-shock conditioning was employed. We have isolated P insertional mutations affecting memory after courtship conditioning -another form of classical conditioning in Drosophila. Here we report the behavioral characteristics of one of these mutants, which we have called nemy (no extended memory).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Short-term memory (STM), lasting on the order of hours, is produced by single training trials or multiple training trials that are not separated in time. STM requires no transcriptional Joiner and Griffith 1997, 2000Kane et al 1997;Savvateeva et al 2000;Sitnik et al 2003;Dukas 2005Kamyshev et al 1999, 2000Kamyshev 2003 Keleman et al 2007 mated-immobile Ejima et al 2005;Kamyshev et al 1999, 2000virgin Kane et al 1997O'Dell et al 1999;McBride et al 1999McBride et al , 2005Reif et al 2002;Dukas 2005 McBride et al 1999; Presente et al 2004 virgin-immobile Siegel and Hall 1979;Tompkins et al 1983;Gailey et al 1984;Cowan and Siegel 1984;Zawistowski 1988;Griffith et al 1993;Joiner and Griffith 1997, 2000Diagana et al 2002;Griffith 2004, 2006;Siwicki et al 2005;Ejima et al 2005;Kamyshev et al 1999Kamyshev et al , 2000Kamyshev et al , 2002 ) chamber where the male would be in almost constant contact with the mated female. Manipulation of the training conditions by increasing the size of the chamber (which allows the male to occasionally ''escape'' the mated female, creating a rest period, see Table 1) or by periodically removing the mated female has been shown to generate a memory that can last up to 8 d (McBride et al 1999).…”
Section: Courtship Behavior Engages Multiple Sensory Systemsmentioning
confidence: 99%
“…Short-term memory (STM), lasting on the order of hours, is produced by single training trials or multiple training trials that are not separated in time. STM requires no transcriptional Joiner and Griffith 1997, 2000Kane et al 1997;Savvateeva et al 2000;Sitnik et al 2003;Dukas 2005Kamyshev et al 1999, 2000Kamyshev 2003 Keleman et al 2007 mated-immobile Ejima et al 2005;Kamyshev et al 1999, 2000virgin Kane et al 1997O'Dell et al 1999;McBride et al 1999McBride et al , 2005Reif et al 2002;Dukas 2005 McBride et al 1999; Presente et al 2004 virgin-immobile Siegel and Hall 1979;Tompkins et al 1983;Gailey et al 1984;Cowan and Siegel 1984;Zawistowski 1988;Griffith et al 1993;Joiner and Griffith 1997, 2000Diagana et al 2002;Griffith 2004, 2006;Siwicki et al 2005;Ejima et al 2005;Kamyshev et al 1999Kamyshev et al , 2000Kamyshev et al , 2002 ) chamber where the male would be in almost constant contact with the mated female. Manipulation of the training conditions by increasing the size of the chamber (which allows the male to occasionally ''escape'' the mated female, creating a rest period, see Table 1) or by periodically removing the mated female has been shown to generate a memory that can last up to 8 d (McBride et al 1999).…”
Section: Courtship Behavior Engages Multiple Sensory Systemsmentioning
confidence: 99%
“…Learning and memory have been demonstrated in various social contexts in fruit flies as well (6,(8)(9)(10)(11). We have been studying aggression as a behavior indicative of individual fitness in fruit flies and other organisms.…”
mentioning
confidence: 99%
“…nemy was originally generated in a forward genetic screen for mutants affecting courtship memory [ 34 ]. A more thorough characterization showed that in addition to defects in courtship memory, nemy mutants also have a defect in middle-term olfactory memory [ 8 ].…”
Section: Resultsmentioning
confidence: 99%